PREVALENCE OF SOME IDENTIFIED PROSTATE PROBLEMS AMONG PEOPLE RESIDENT IN IMO STATE, NIGERIA. - A. U., Opara,; G. C., Uloneme,; P., Nwankpa,; D., Akukwu,; J., Ekezie (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
Adult males aged forty years and above resident in Imo State (both indigenes and non indigenes) who visited the state owned health institutions in the state and also the Federal Medical Centre Owerri constituted the population of the study. A sample size of one thousand and ten (1010) patients’ case records/reports were on request, made available, randomly from the institutions’ records departments for a survey. A careful investigation of the case records showed that as many as three hundred and twenty six (326) of the patients (representing 32.3%) were diagnosed, managed or treated of prostate related problems, identified as benign prostatic hyperplasia (BPH), prostatitis or cancer of the prostate. The prevalence of these prostate problems was also seen to increase with age, as observed in people above seventy years of age where over 48% of them was diagnosed of one form of prostate problem or the other. Sadly, again, the results of the study showed that the prevalence of prostate problems among adult males resident in Imo State increased as the years passed by.